2016
DOI: 10.1016/j.aip.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

The appeal of sad music: A brief overview of current directions in research on motivations for listening to sad music

Abstract: Sadness is the most common emotion attributed to music after happiness. A recent surge in research has explored why sad music is so popular. This work aimed to summarise the results of these studies. It is indicated that sad music is listened to more commonly in sad mood and negative situation. Many different motivations have been found with regards to listening to sad music such as validating emotions, providing solace, providing rewarding emotional experiences, and aiding reflection and relaxation. With rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 43 publications
2
27
0
Order By: Relevance
“…None of these music listening strategies was associated with stress, and two of these music listening strategies (diversion and entertainment) were not associated with depression or anxiety. Moreover, the use of music for diversion and entertainment have clearly been related to enhancing mood or maintaining positive mood (Van den Tol & Giner-Sorolla, 2016), whereas the use of music for mental work regards contemplation and clarification of emotional preoccupations (Saarikallio, 2008), which is a process that can free a person of negative affect (Chin & Rickard, 2013; Van den Tol, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…None of these music listening strategies was associated with stress, and two of these music listening strategies (diversion and entertainment) were not associated with depression or anxiety. Moreover, the use of music for diversion and entertainment have clearly been related to enhancing mood or maintaining positive mood (Van den Tol & Giner-Sorolla, 2016), whereas the use of music for mental work regards contemplation and clarification of emotional preoccupations (Saarikallio, 2008), which is a process that can free a person of negative affect (Chin & Rickard, 2013; Van den Tol, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…While people outside subculture understand that teenagers are reinforced with suicidal thought and self-injury by emo music, emo fan scholars reported that these fans stopped cutting themselves after being coped by such the music [21], [37]. To identify with sad music is a part of coping skills that help people accept and make sense with negative event in their life [38], [39]. Sad emo songs were easily used as coping tools by their fans, since the lyrics are about problems with friends, family, heartbreaking, and loneliness [27], [40], [41].…”
Section: Hypotheses Constructionmentioning
confidence: 99%
“…As such the differences observed between conditions could be a product of the experimenter-selected music conveying a sadder emotion and resulting in a slower shift away from sadness, in line with Randall and Rickard's (2017) results. However, the difference could also be in-part due to familiarity and preference for the song listened allowing for a faster return to baseline than music which does not have prior associations (van Goethem & Sloboda, 2011;van den Tol, 2016). As such future studies on emotion congruent music should make greater efforts to hold emotion consistent across self and experimenter-selected music (i.e.…”
Section: Listening To Music When Sadmentioning
confidence: 99%